Diabetes care in refugee camps: The experience of UNRWA. Issue 1 (April 2015) - Shahin, Yousef; Kapur, Anil; Seita, Akhiro
Abstract United Nations Relief and Works Agency for Palestine Refugees in the Near East (UNRWA) was established in 1949 and has delivered health care services for over 65 years. The epidemiological transition in disease burden is changing the context in which UNRWA's health programme operates and poses new challenges that require new ways of providing health services. Hypertension and diabetes are two major health problems for Palestine refugees. UNRWA has been providing diabetes and hypertension care since 1992 in its primary health care centres. Of late, through a structured process of care delivery the UNRWA health system is making significant strides in addressing diabetes and hypertension and consequently the nine voluntary global targets as envisaged in the WHO Global Action Plan for the Prevention and Control of NCDs 2013–2020. Given that most developing countries either have no or only rudimentary services for diabetes and hypertension at the primary care level and may face similar resource and capacity constraints, UNRWA's efforts can serve as a model and inspiration to set up similar initiatives.